Response of microbial communities and physical and chemical properties in inoculated soils with Fusarium oxysporum Schl. F. sp. Benincasae to different root exudates resistant to fusarium wilt - Wu, Haolong; Fu, Junyu; Liao, Daolong; Chen, Yilin; Zhao, Zhen; Liu, Zifan; Zhou, Bin (Frontiers in Microbiology, 2025)
Wax gourd wilt (WGW) is a destructive soil-borne disease, and grafting pumpkin rootstocks offers effective and eco-friendly control. “Haizhan 1” pumpkin rootstock exhibits superior disease resistance compared to Cucurbita ficifolia, with root exudates improving soil microecology. However, the specific root exudate components involved in wilt resistance and their effects on soil microbial diversity remain unclear. In this paper, “Haizhan 1” pumpkin, Cucurbita ficifolia pumpkin and “Tiezhu 168” wax gourd are taken as rootstock materials to graft and obtain the five kinds of experimental subjects (H_T, B_T, H_H, B_B, T_T). Root exudates from five grafted combinations were analyzed by using metabolomics. Ten key metabolites that have direct fungicidal effects and indirect regulatory effects on disease resistance were identified, including Melilotoside A, a substance unique to pumpkin-wax gourd grafting. Potted experiments revealed that root exudates from resistant (H_T), moderately resistant (B_T), and susceptible (T_T) plants altered soil microbial communities under Fusarium oxysporum challenge. High-throughput sequencing identified six key bacteria linked to disease resistance: norank_f__norank_o_0319-6G20, Haliangium, norank_f__norank_o__norank_c__OLB14, Thermomonas, Brevundimonas, and Gemmatimonas. Correlation analysis highlighted the interaction between root exudate metabolites and soil microbes. This study clarifies the role of root exudates in WGW resistance and provides a foundation for developing biocontrol strategies.